The Role of Alcohol, LPS Toxicity, and ALDH2 in Dental Bony Defects - Hsiao-Cheng Tsai; Che-Hong Chen; Daria Mochly-Rosen; Yi-Chen Ethan Li; Min-Huey Chen (Biomolecules, 2021)
It is estimated that 560 million people carry an East Asian-specific ALDH2*2 dominant-negative mutation which leads to enzyme inactivation. This common ALDH2 polymorphism has a significant association with osteoporosis. We hypothesized that the ALDH2*2 mutation in conjunction with periodontal Porphyromonas gingivalis bacterial infection and alcohol drinking had an inhibitory effect on osteoblasts and bone regeneration. We examined the prospective association of ALDH2 activity with the proliferation and mineralization potential of human osteoblasts in vitro. The ALDH2 knockdown experiments showed that the ALDH2 knockdown osteoblasts lost their proliferation and mineralization capability. To mimic dental bacterial infection, we compared the dental bony defects in wild-type mice and ALDH2*2 knockin mice after injection with purified lipopolysaccharides (LPS), derived from P. gingivalis which is a bacterial species known to cause periodontitis. Micro-computed tomography (micro-CT) scan results indicated that bone regeneration was significantly affected in the ALDH2*2 knockin mice with about 20% more dental bony defects after LPS injection than the wild-type mice. Moreover, the ALDH2*2 knockin mutant mice had decreased osteoblast growth and more dental bone loss in the upper left jaw region after LPS injection. In conclusion, these results indicated that the ALDH2*2 mutation with alcohol drinking and chronic exposure to dental bacterial-derived toxin increased the risk of dental bone loss.